Ultrahigh-temperature ceramic composite material and preparation method thereof
By optimizing the preparation process flow, using CVI technology and discharge plasma sintering technology, Cf/HfC-ZrB2-SiC-ZrC composites are prepared, solving the challenges of ultra-high temperature ceramic matrix composites in terms of bending strength and ablation resistance, achieving higher performance and lower cost efficiency.
Patent Information
- Application Number
- CN202510072634.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-15
AI Technical Summary
Ultra-high temperature ceramic matrix composites still face challenges in the large-scale application and cost efficiency of materials, especially in terms of bending strength and ablation resistance.
By optimizing the preparation process flow, Cf/HfC matrix is prepared using CVI technology, and ZrB2 and ZrC are deposited step by step on its surface, followed by impregnation, curing, cracking and discharge plasma sintering, and finally obtaining Cf/HfC-ZrB2-SiC-ZrC composite material.
It effectively improves the bending strength and ablation resistance of ultra-high temperature ceramic composite materials, achieving higher performance indicators and lower cost efficiency.
Smart Images

Figure CN119822837A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic preparation, and in particular to an ultra-high temperature ceramic composite material and a preparation method thereof. Background Art
[0002] The high performance and versatility of ultra-high temperature ceramic matrix composites have led to their application in a variety of fields. Although significant research progress has been made in this field both at home and abroad, there are still challenges in the large-scale application and cost efficiency of materials, which requires in-depth exploration and technological innovation in future research. Through a comprehensive analysis of the literature, it can be seen that the research on ultra-high temperature ceramic matrix composites is a highly active and rapidly developing field, and continuous technological innovation and in-depth functional exploration will lay a solid foundation for future practical applications. Summary of the invention
[0003] The purpose of the present invention is to provide an ultra-high temperature ceramic composite material and a preparation method thereof, and to effectively improve the bending strength and ablation resistance of the ultra-high temperature ceramic composite material by optimizing the preparation process.
[0004] To achieve the above object, the present invention provides an ultra-high temperature ceramic composite material, the ultra-high temperature ceramic composite material is C f / HfC-ZrB2-SiC-ZrC composite materials.
[0005] The present invention provides a method for preparing an ultra-high temperature ceramic composite material, comprising the following steps:
[0006] Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform;
[0007] Step 2: Preparation of C by CVI technology f / HfC matrix;
[0008] Step 3: In C f ZrB2 and ZrC were deposited step by step on the surface of C / HfC substrate to prepare f / HfC-ZrB2-ZrC precursor;
[0009] Step 4: C f The HfC-ZrB2-ZrC precursor material is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor;
[0010] Step 5: C f / HfC-ZrB2-SiC-ZrC precursor was pressed and dried, and the dried C was sintered by spark plasma sintering technology. f / HfC-ZrB2-SiC-ZrC precursor is sintered to obtain C f / HfC-ZrB2-SiC-ZrC composite materials.
[0011] Preferably, the specific operation of step one is: weaving the carbon fibers into a three-dimensional structure shape, and making the carbon fibers into a carbon fiber preform by a needle punching process.
[0012] Preferably, the specific operation of step 2 is: in an inert gas atmosphere, a clean and dry crucible containing HfCl4 is placed in a low temperature zone of a chemical vapor deposition furnace, and at the same time, a carbon fiber preform is placed in a high temperature zone of a chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, a dilution gas is introduced and the temperature is increased, after the temperature is increased, methane gas and an inert gas are introduced, and after the reaction, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
[0013] Preferably, the specific operation of step three is: using BCl3 as a boron source, hydrogen as a reducing gas, and argon as a diluent gas, ZrCl4 and the above gases are introduced into a CVD reaction chamber to undergo a chemical reaction to generate ZrB2 and deposit it on C f The surface of the HfC matrix is C f / HfC-ZrB2 material;
[0014] Then, methane gas and ZrCl4 gas are introduced into the CVD reaction chamber to react chemically to generate ZrC which is then deposited on the Cf / HfC-ZrB2 material to finally obtain C f / HfC-ZrB2-ZrC precursor.
[0015] Preferably, the specific operation of step 4 is: preparing an impregnation solution containing a SiC precursor, f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor.
[0016] Preferably, in step 1, the carbon fiber is PAN-based carbon fiber.
[0017] Preferably, in step 2, the heating rate is 10-30°C / min, the high temperature zone is heated to 1000-1500°C, the low temperature zone is heated to 200-250°C, the dilution gas is hydrogen, the hydrogen flow rate is 0.1-0.5L / min, the inert gas is argon, the argon flow rate is 10-50mL / min, the methane gas flow rate is 10-20mL / min, and the reaction time is 4-6h.
[0018] Preferably, in step three, the temperature for depositing ZrB2 is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h; the temperature for depositing ZrC is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h.
[0019] Preferably, in step 4, polycarbosilane is used as the impregnating agent, the impregnation time is 1-24 hours, the number of impregnations is 3-5 times, the cross-linking curing temperature is 150-200°C, the curing time is 2-6 hours, the high temperature pyrolysis temperature is 1000-1500°C, the high temperature pyrolysis time is 3-8 hours, and the heating rate is 1-5°C / min.
[0020] Therefore, the present invention adopts the above-mentioned ultra-high temperature ceramic composite material and preparation method, and optimizes the preparation process flow to effectively improve the bending strength and ablation resistance of the ultra-high temperature ceramic composite material.
[0021] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is an electron microscope image of Example 1 of an ultra-high temperature ceramic composite material and a preparation method of the present invention;
[0023] Figure 2 It is a preparation flow chart of Example 1 of an ultra-high temperature ceramic composite material and a preparation method of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0025] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0026] The present invention provides an ultra-high temperature ceramic composite material, wherein the ultra-high temperature ceramic composite material is C f / HfC-ZrB2-SiC-ZrC composite materials.
[0027] The present invention provides a method for preparing an ultra-high temperature ceramic composite material, comprising the following steps:
[0028] Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform. The specific operation is: select PAN-based carbon fiber, weave the carbon fiber into a three-dimensional structure, and make the carbon fiber into a carbon fiber preform through a needle punching process.
[0029] Step 2: Preparation of C by CVI technology f / HfC matrix, the specific operation is: in an inert gas atmosphere, a clean and dry crucible containing HfCl4 is placed in the low temperature zone of a chemical vapor deposition furnace, and at the same time, a carbon fiber preform is placed in the high temperature zone of the chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, a dilution gas is introduced and the temperature is increased, after the temperature is increased, methane gas and an inert gas are introduced, and after the reaction, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
[0030] In step 2, the heating rate is 10-30°C / min, the high temperature zone is heated to 1000-1500°C, the low temperature zone is heated to 200-250°C, the dilution gas is hydrogen, the hydrogen flow rate is 0.1-0.5L / min, the inert gas is argon, the argon flow rate is 10-50mL / min, the methane gas flow rate is 10-20mL / min, and the reaction time is 4-6h.
[0031] Step 3: In C f ZrB2 and ZrC were deposited on the surface of the C / HfC substrate in steps to prepare f / HfC-ZrB2-ZrC precursor, the specific operation is: use BCl3 as the boron source, hydrogen as the reducing gas, argon as the diluent gas, pass ZrCl4 and the above gases into the CVD reaction chamber to react chemically to generate ZrB2 and deposit it on C f The surface of the HfC matrix is C f / HfC-ZrB2 material;
[0032] Then, methane gas and ZrCl4 gas are introduced into the CVD reaction chamber to react chemically to generate ZrC which is then deposited on the Cf / HfC-ZrB2 material to finally obtain C f / HfC-ZrB2-ZrC precursor.
[0033] In step 3, the temperature for depositing ZrB2 is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h; the temperature for depositing ZrC is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h.
[0034] Step 4: C f The precursor of / HfC-ZrB2-ZrC is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor, the specific operation is: prepare an impregnation solution containing SiC precursor, f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor.
[0035] In step 4, polycarbosilane is used as the impregnating agent, the impregnation time is 1-24 hours, the number of impregnations is 3-5 times, the cross-linking curing temperature is 150-200°C, the curing time is 2-6 hours, the high temperature pyrolysis temperature is 1000-1500°C, the high temperature pyrolysis time is 3-8 hours, and the heating rate is 1-5°C / min.
[0036] Step 5: C f The HfC-ZrB2-SiC-ZrC precursor was pressed and dried, and the dried C f / HfC-ZrB2-SiC-ZrC precursor is sintered at a temperature of 1400-1700°C. Vacuuming is required during sintering to obtain C f / HfC-ZrB2-SiC-ZrC composite materials.
[0037] Embodiment 1
[0038] like Figure 2 As shown, the present invention provides a method for preparing an ultra-high temperature ceramic composite material, comprising the following steps:
[0039] Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform. The specific operation is: select PAN-based carbon fiber, weave the carbon fiber into a three-dimensional structure, and form the carbon fiber preform through a needle punching process.
[0040] Step 2: Preparation of C by CVI technology f / HfC matrix, the specific operation is: under Ar atmosphere, a clean and dry crucible containing HfCl4 is placed in the low temperature zone of the chemical vapor deposition furnace, and the carbon fiber preform is placed in the high temperature zone of the chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, hydrogen is introduced and the temperature is increased, the hydrogen flow rate is 0.1L / min, the heating rate is 10℃ / min, the high temperature zone is heated to 1000℃, and the low temperature zone is heated to 200℃. After the heating is completed, methane gas and inert gas are introduced, the inert gas is argon, the argon flow rate is 10mL / min, and the methane flow rate is 10mL / min. After the reaction for 4h, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
[0041] Step 3: In C f ZrB2 and ZrC were deposited on the surface of the C / HfC substrate in steps to prepare f / HfC-ZrB2-ZrC precursor, the specific operation is: take BCl3 as boron source, hydrogen as reducing gas, argon as diluent gas, introduce ZrCl4 and the above gases into the CVD reaction chamber to react chemically to generate ZrB2, the temperature is 1000℃, the pressure during the reaction is 10Torr, the reaction time is 1h, and it is deposited on C f The surface of the HfC matrix is C f / HfC-ZrB2 material;
[0042] Then, methane gas and ZrCl4 gas are introduced into the CVD reaction chamber to react chemically to generate ZrC at a temperature of 1000°C, a pressure of 10 Torr, and a reaction time of 1 h, and then deposited on C f / HfC-ZrB2 material finally obtained C f / HfC-ZrB2-ZrC precursor.
[0043] Step 4: C f The precursor of / HfC-ZrB2-ZrC is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor, the specific operation is: prepare an impregnation solution containing SiC precursor, use polycarbosilane as an impregnation agent, the impregnation time is 5h, the impregnation number is 3 times, C f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor, the cross-linking curing temperature is 150℃ for 2h, the high temperature pyrolysis temperature is 1000℃ for 3h, and the heating rate is 3℃ / min.
[0044] Step 5: C f / HfC-ZrB2-SiC-ZrC precursor was pressed and dried, and the dried C was sintered by spark plasma sintering technology. f / HfC-ZrB2-SiC-ZrC precursor is sintered at a temperature of 1400°C and vacuum is required during sintering to obtain C f / HfC-ZrB2-SiC-ZrC composite materials, such as Figure 1 shown.
[0045] Embodiment 2
[0046] The present invention provides a method for preparing an ultra-high temperature ceramic composite material, comprising the following steps:
[0047] Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform. The specific operation is: select PAN-based carbon fiber, weave the carbon fiber into a three-dimensional structure, and form the carbon fiber preform through a needle punching process.
[0048] Step 2: Preparation of C by CVI technology f / HfC matrix, the specific operation is: under Ar atmosphere, a clean and dry crucible containing HfCl4 is placed in the low temperature zone of the chemical vapor deposition furnace, and the carbon fiber preform is placed in the high temperature zone of the chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, hydrogen is introduced and the temperature is increased, the hydrogen flow rate is 0.3L / min, the heating rate is 20℃ / min, the high temperature zone is heated to 1250℃, and the low temperature zone is heated to 220℃. After the heating is completed, methane gas and inert gas are introduced, the inert gas is argon, the argon flow rate is 25mL / min, and the methane flow rate is 15mL / min. After the reaction for 5h, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
[0049] Step 3: In C f ZrB2 and ZrC were deposited on the surface of the C / HfC substrate in steps to prepare f / HfC-ZrB2-ZrC precursor, the specific operation is: take BCl3 as boron source, hydrogen as reducing gas, argon as diluent gas, introduce ZrCl4 and the above gases into the CVD reaction chamber to react chemically to generate ZrB2, the temperature is 1300℃, the pressure during the reaction is 50Torr, the reaction time is 3h, and it is deposited on C fThe surface of the HfC matrix is C f / HfC-ZrB2 material;
[0050] Then, methane gas and ZrCl4 gas were introduced into the CVD reaction chamber to react chemically to generate ZrC at a temperature of 1300°C, a pressure of 50 Torr, and a reaction time of 3 h, and then deposited on C f / HfC-ZrB2 material finally obtained C f / HfC-ZrB2-ZrC precursor.
[0051] Step 4: C f The precursor of / HfC-ZrB2-ZrC is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor, the specific operation is: prepare an impregnation solution containing SiC precursor, use polycarbosilane as an impregnation agent, the impregnation time is 10h, the impregnation number is 4 times, C f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor, the cross-linking curing temperature is 170℃ for 4h, the high temperature pyrolysis temperature is 1300℃ for 5h, and the heating rate is 5℃ / min.
[0052] Step 5: C f The HfC-ZrB2-SiC-ZrC precursor was pressed into shape and dried, and the C obtained in step 4 was sintered by spark plasma sintering technology. f / HfC-ZrB2-SiC-ZrC precursor is sintered at a temperature of 1500°C and vacuum is required during sintering to obtain C f / HfC-ZrB2-SiC-ZrC composite materials.
[0053] Embodiment 3
[0054] The present invention provides a method for preparing an ultra-high temperature ceramic composite material, comprising the following steps:
[0055] Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform. The specific operation is: select PAN-based carbon fiber, weave the carbon fiber into a three-dimensional structure, and form the carbon fiber preform through a needle punching process.
[0056] Step 2: Preparation of C by CVI technology f / HfC matrix, the specific operation is: under Ar atmosphere, a clean and dry crucible containing HfCl4 is placed in the low temperature zone of the chemical vapor deposition furnace, and the carbon fiber preform is placed in the high temperature zone of the chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, hydrogen is introduced and the temperature is increased, the hydrogen flow rate is 0.5L / min, the heating rate is 30℃ / min, the high temperature zone is heated to 1500℃, and the low temperature zone is heated to 250℃. After the heating is completed, methane gas and inert gas are introduced, the inert gas is argon, the argon flow rate is 50mL / min, and the methane flow rate is 20mL / min. After the reaction for 6h, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
[0057] Step 3: In C f ZrB2 and ZrC were deposited on the surface of the C / HfC substrate in steps to prepare f / HfC-ZrB2-ZrC precursor, the specific operation is: take BCl3 as boron source, hydrogen as reducing gas, argon as diluent gas, introduce ZrCl4 and the above gases into the CVD reaction chamber to react chemically to generate ZrB2, the temperature is 1500℃, the pressure during the reaction is 100Torr, the reaction time is 5h, and it is deposited on C f The surface of the HfC matrix is C f / HfC-ZrB2 material;
[0058] Then, methane gas and ZrCl4 gas were introduced into the CVD reaction chamber to react chemically to generate ZrC at a temperature of 1500°C, a pressure of 100 Torr, and a reaction time of 5 h, and then deposited on C f / HfC-ZrB2 material finally obtained C f / HfC-ZrB2-ZrC precursor.
[0059] Step 4: C f The precursor of / HfC-ZrB2-ZrC is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor, the specific operation is: prepare an impregnation solution containing SiC precursor, use polycarbosilane as an impregnation agent, the impregnation time is 15h, the impregnation number is 5 times, C f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor, the cross-linking curing temperature is 200℃ for 6h, the high temperature pyrolysis temperature is 1500℃ for 8h, and the heating rate is 5℃ / min.
[0060] Step 5: C f The HfC-ZrB2-SiC-ZrC precursor was pressed into shape and dried, and the C obtained in step 4 was sintered by spark plasma sintering technology. f / HfC-ZrB2-SiC-ZrC precursor is sintered at a temperature of 1700°C and vacuum is required during sintering to obtain C f / HfC-ZrB2-SiC-ZrC composite materials.
[0061] The products obtained from Examples 1 to 3 were tested for performance.
[0062] The sample was machined into a size of Φ30mm×10mm for oxyacetylene ablation test. The line ablation rate and mass ablation rate at 2500℃ were calculated. The bending resistance of the product was tested at 2000℃. The performance test results are shown in Table 1.
[0063] Table 1 Performance test results
[0064] Line ablation rate Mass ablation rate Bending strength Embodiment 1 3.4μm / s 26.2μm / s 404MPa Embodiment 2 3.3μm / s 25.3μm / s 405MPa Embodiment 3 4.1μm / s 27.1μm / s 401MPa
[0065] It can be seen from the above table that the prepared ultra-high temperature ceramic composite material has a linear ablation rate lower than 5μm / s, a mass ablation rate lower than 30μm / s, and a flexural strength of 400MPa, indicating that the ultra-high temperature ceramic composite material has high flexural strength, low mass ablation rate and linear ablation rate, indicating that the ultra-high temperature ceramic composite material has good ablation resistance.
[0066] Therefore, the present invention adopts the above-mentioned ultra-high temperature ceramic composite material and preparation method, and optimizes the preparation process flow to effectively improve the bending strength and ablation resistance of the ultra-high temperature ceramic composite material.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An ultra-high temperature ceramic composite material, characterized in that: Ultra-high temperature ceramic composite material is C f / HfC-ZrB2-SiC-ZrC composite materials.
2. The method for preparing an ultra-high temperature ceramic composite material according to claim 1, characterized in that: The following steps are involved: Step 1: Select carbon fiber and prepare the carbon fiber into a carbon fiber preform; Step 2: Preparation of C by CVI technology f / HfC matrix; Step 3: In C f ZrB2 and ZrC were deposited step by step on the surface of C / HfC substrate to prepare f / HfC-ZrB2-ZrC precursor; Step 4: C f The HfC-ZrB2-ZrC precursor material is pretreated and then impregnated, and the impregnated material is solidified, cracked, and post-treated to finally obtain C f / HfC-ZrB2-SiC-ZrC precursor; Step 5: C f / HfC-ZrB2-SiC-ZrC precursor was pressed and dried, and the dried C was sintered by spark plasma sintering technology. f / HfC-ZrB2-SiC-ZrC precursor is sintered to obtain C f / HfC-ZrB2-SiC-ZrC composite materials.
3. The method for preparing an ultra-high temperature ceramic composite material according to claim 2, characterized in that: The specific operation of step one is: weaving the carbon fiber into a three-dimensional structural shape, and making the carbon fiber into a carbon fiber preform through a needle punching process.
4. The method for preparing an ultra-high temperature ceramic composite material according to claim 2, characterized in that: The specific operation of step 2 is as follows: in an inert gas atmosphere, a clean and dry crucible containing HfCl4 is placed in the low temperature zone of a chemical vapor deposition furnace, and at the same time, a carbon fiber preform is placed in the high temperature zone of a chemical vapor deposition furnace, the chemical vapor deposition furnace is evacuated, a dilution gas is introduced and the temperature is increased, and after the temperature is increased, methane gas and an inert gas are introduced, and after the reaction, the gas is stopped from being introduced into the furnace, and the temperature in the furnace naturally drops to room temperature under vacuum to obtain C f / HfC matrix.
5. The method for preparing an ultra-high temperature ceramic composite material according to claim 2, characterized in that: The specific operation of step three is: using BCl3 as the boron source, hydrogen as the reducing gas, and argon as the diluent gas, ZrCl4 and the above gases are introduced into the CVD reaction chamber to undergo a chemical reaction to generate ZrB2 and deposit it on the C f The surface of the HfC matrix is C f / HfC-ZrB2 material; Then, methane gas and ZrCl4 gas are introduced into the CVD reaction chamber to react chemically to generate ZrC which is then deposited on the Cf / HfC-ZrB2 material to finally obtain C f / HfC-ZrB2-ZrC precursor.
6. The method for preparing an ultra-high temperature ceramic composite material according to claim 2, characterized in that: The specific operation of step 4 is: prepare an impregnation solution containing SiC precursor, f The HfC-ZrB2-ZrC precursor is immersed in the impregnation solution, cross-linked and cured, and pyrolyzed at high temperature to convert the SiC precursor into SiC and deposit on the C f / HfC-ZrB2-ZrC precursor, and finally C f / HfC-ZrB2-SiC-ZrC precursor.
7. The method for preparing an ultrahigh temperature ceramic composite material according to claim 3, characterized in that: In step 1, the carbon fiber is selected as PAN-based carbon fiber.
8. The method for preparing an ultra-high temperature ceramic composite material according to claim 4, characterized in that: In step 2, the heating rate is 10-30°C / min, the high temperature zone is heated to 1000-1500°C, the low temperature zone is heated to 200-250°C, the dilution gas is hydrogen, the hydrogen flow rate is 0.1-0.5L / min, the inert gas is argon, the argon flow rate is 10-50mL / min, the methane gas flow rate is 10-20mL / min, and the reaction time is 4-6h.
9. The method for preparing an ultrahigh temperature ceramic composite material according to claim 5, characterized in that: In step 3, the temperature for depositing ZrB2 is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h; the temperature for depositing ZrC is 1000-1500°C, the pressure for the reaction is 10-100Torr, and the reaction time is 1-5h.
10. The method for preparing an ultra-high temperature ceramic composite material according to claim 6, characterized in that: In step 4, polycarbosilane is used as the impregnating agent, the impregnation time is 1-24 hours, the number of impregnations is 3-5 times, the cross-linking curing temperature is 150-200°C, the curing time is 2-6 hours, the high temperature pyrolysis temperature is 1000-1500°C, the high temperature pyrolysis time is 3-8 hours, and the heating rate is 1-5°C / min.